Wildwood imperium ebook - Meloy, Colin (The Wildwood Chronicles, 2014)
From Colin Meloy, lead singer of the Decemberists, and Carson Ellis, acclaimed illustrator of The Mysterious Benedict Society, comes the stunning third book in the New York Times bestselling fantasy-adventure series the Wildwood Chronicles. A young girl's midnight séance awakens a long-slumbering malevolent spirit.... A band of runaway orphans allies with an underground collective of saboteurs and plans a daring rescue of their friends, imprisoned in the belly of an industrial wasteland.... Two old friends draw closer to their goal of bringing together a pair of exiled toy makers in order to reanimate a mechanical boy prince.... As the fate of Wildwood hangs in the balance. The Wildwood Chronicles is a mesmerizing and epic tale, at once firmly steeped in the classics of children's literature and completely fresh at the same time. In this book, Colin Meloy continues to expand and enrich the magical world and cast of characters he created in Wildwood, while Carson Ellis once again brings that world to life with her gorgeous artwork, including six full-color plates.